Speed and Position Estimator of Dual-PMSM for Independent Control Drives using Five-Leg Inverter - Jurifa Mat Lazi; Zulkifilie Ibrahim; MD Hairul Talib; Auzani Jidin; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Nowadays, A lot of industry requires Multi Motor System (MMS) applications such as propulsion and traction power, HEV, conveyer and air-conditioner. The Conventional arrangement for MMS usually done by cascading the motors drives which each drives has individual inverter. Part of MMS, Dual-Motor drives fed by a single inverter is being paid attention by the researchers. Dual-motor drives using a single three-leg inverter has its limitation in the case of different operating conditions and independent speed control requirement. Therefore, dual-Motor drives using a single Five-leg Inverter (FLI) was proposed for independent control for both motors. In PMSM drives, the information of the feedback speed and rotor angular position is compulsory for variable speed drives. Conventional solution is by using speed sensor which will increase size, cost, extra hardwire and feedback devices, especially for the case of dual-PMSM drives. The best solution to overcome this problem is by eliminating the usage of speed and position sensors for Dual-motor drives. This paper presents a new sensorless strategy using speed and position estimator for Independent Dual- Permanent Magnet Synchronous Machine (PMSM) drives which utilize Five-Leg Inverter (FLI). The proposed strategy is simulated using MATLAB/Simulink to evaluate the overall motor drive performance. Meanwhile the experimental set-up is connected to dSPACE 1103 Board. The experimental results demonstrate that the proposed estimator is successfully managed to control the Dual-PMSM drives for variation of speed and for different direction applications.